#TITLE_ALTERNATIVE# - MAKARIM BASUKI (NIM : 10212044), RAYHAN
Geoelectricity survey using resistivity measurement is a common thing today. With this resistivity measurement method, any anomaly in earth subsurface can be found, without leaving any damage to the top soil. The price of this tool is expensive. Thus, this study is done to make a prototype design that can be used as a base for a blueprint for this tool production. A program is also needed to get more information from the observed data. An inversion program will be created for 1D data, to estimate the subsurface true model. As for 2D data, a program will be created to produce an apparent resistivity pseudesection . Isis Proteus will be used to make sure wether the design is usable or not, by comparing the observed data with the true value.For the inversion program , a test will be held by using a homogenous and heteregenous subsurface model, with initial model that is widely differnt from the true model. As for the 2D program, will be tested by creating a pseudsection of multilayered earth without any horizontal variation. The results show that both the design and the program can be used as a basi for further development of the arduino based resistivity measuring device